2020
DOI: 10.7717/peerj.8740
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel in vitro insulin resistance model in primary human tenocytes for diabetic tendinopathy research

Abstract: Background Type 2 diabetes mellitus (T2DM) had been reported to be associated with tendinopathy. However, the underlying mechanisms of diabetic tendinopathy still remain largely to be discovered. The purpose of this study was to develop insulin resistance (IR) model on primary human tenocytes (hTeno) culture with tumour necrosis factor-alpha (TNF-α) treatment to study tenocytes homeostasis as an implication for diabetic tendinopathy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In addition, tendon homeostasis is modulated by MMPs and TIMPs (tissue inhibitors of MMPs), which regulates the production of collagen and non-collagen matrix by tenocytes. Thus, it was shown that IR positively regulates the expression of MMP-9, highlighted here, and MMP-13 (24). Another study demonstrated that RSV, as an antioxidant, can decrease MMP-9 expression not only by suppressing MMP-9 production but also by augmenting tissue inhibitors of metalloproteinases (TIMPs) production (25).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, tendon homeostasis is modulated by MMPs and TIMPs (tissue inhibitors of MMPs), which regulates the production of collagen and non-collagen matrix by tenocytes. Thus, it was shown that IR positively regulates the expression of MMP-9, highlighted here, and MMP-13 (24). Another study demonstrated that RSV, as an antioxidant, can decrease MMP-9 expression not only by suppressing MMP-9 production but also by augmenting tissue inhibitors of metalloproteinases (TIMPs) production (25).…”
Section: Discussionmentioning
confidence: 88%